2022
DOI: 10.3389/fimmu.2022.977377
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of Belimumab combined with standard therapy in severe active lupus nephritis requiring kidney replacement therapy: A case report and literature review

Abstract: Lupus Nephritis (LN) is the most common manifestation of severe organ damage for systemic lupus erythematosus (SLE) patients. Severe active LN could result in acute kidney injury (AKI), which could even require Kidney Replacement Therapy (KRT). Therefore, there needs to be a more proactive and safe induction therapy to quickly and effectively control renal immune inflammation, maintain kidney function or reverse kidney damage. While multiple clinical studies have proven the efficacy and safety of Belimumab in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Zhang C et al. reported similar results [ 41 ]. These results showed that belimumab was able to increase urine output and reduce the incidence of dialysis dependence, induce immunologic remission and decrease the disease activity of SLE in patients receiving dialysis treatment.…”
Section: Discussionsupporting
confidence: 56%
“…Zhang C et al. reported similar results [ 41 ]. These results showed that belimumab was able to increase urine output and reduce the incidence of dialysis dependence, induce immunologic remission and decrease the disease activity of SLE in patients receiving dialysis treatment.…”
Section: Discussionsupporting
confidence: 56%